Factors related to mortality by pneumonia unrelated to mechanical ventilation - Jucinay Phaedra Silva Sanches; Carla Fernanda Tiroli; Erika Bernardo da Silva; Gabriela Machado Ezaias Paulino; Gilselena Kerbauy; Renata Aparecida Belei; Flávia Meneguetti Pieri (Universidade Federal do Ceará, 2021)
Objective: to analyze the factors related to mortality by nosocomial pneumonia unrelated to mechanical ventilation. Methods: retrospective cohort study with a sample acquired using the 538 notification forms for health care-related infections. The relative risk was calculated and a multivariable analysis was carried out using Poisson regression with a significance level of 5%. Results: the multivariable analysis showed that being under 59 years old and taking only one antimicrobial drug were protective factors against death. The main microorganisms responsible for the increase in the risk of death were: Acinetobacter baumannii, Klebsiella pneumoniae and species of Candida (Candida spp). Conclusion: the factors related to mortality were being 60 years old or older, using two or more antimicrobial substances, and being affected by the microorganisms Acinetobacter baumannii, Klebsiella pneumonia, and species of Candida (Candida spp).